Lithology-specific influence of particle size distribution and mineralogical composition on thermal conductivity measurements of rock fragments - Kämmlein, Marion; Stollhofen, Harald (Geothermics, 2019)
Thermal conductivity data from reservoir rocks are key parameters for the analysis of heat transfer processes and heat flow patterns in geothermal exploration. Laboratory measurements of regional sample sets still provide the most reliable database. Since well cores are rarely available, rock fragments (e.g., drill cuttings) are the most common sample type for laboratory thermal conductivity measurements. However, the effects of the particle size of the rock fragments on the determination of thermal conductivity have not yet been discussed in a systematic study for different rock types. In this study, we used a line source device to investigate the influence of the particle size distribution of rock fragments and powder samples from different rock types on thermal conductivity measurements. The study focuses on three main objectives: <dl> 1. Does the particle size distribution of rock fragments impact thermal conductivity measurements of sample–water mixtures with a line source? 2. Are there lithology-specific differences in suitable particle sizes for measurements of thermal conductivity? 3. Is there an ‘ideal’ or an inappropriate particle size for measurements of rock fragments? </dl> Our study demonstrates that particle size effects on thermal conductivity determination of rock fragments and powders are unequivocal and that the accuracy of thermal conductivity determination can be improved by consideration of suitable, lithology-specific particle size ranges. The accuracy of measurement is related to the particle size distribution, mineralogical composition, competence under mechanical stress, and porosity of the sample–water mixtures during the measurement. For almost monomineralic limestones without significant clay volume fractions, powder samples with particle sizes ≤0.063 mm are most appropriate. In the case of argillaceous sandstone, powder samples are an inappropriate sample type, and instead, coarse rock fragment samples with mean particle sizes of 0.9–1.3 mm are recommended.
Keywords: Thermal conductivity; Particle size; Rock fragments; Mineralogical composition; Powder; Drill cuttings

New thermophysical data pool for NE-Bavaria reveals exceptionally high heat fluxes - Kämmlein, Marion; Bauer, Wolfgang; Stollhofen, Harald (German Geothermal Congress GGC 2017, 2017)
A geothermal anomaly in the Franconian Basin/NE Bavaria was already described in the 1980s and further specified in the 2000s. An undisturbed temperature log in a 1309 m deep well provided a geothermal gradient (gradT) of 4.8 K/100m. The enhanced geothermal gradients led to the development of several balneological facilities in the area. However, heat flux in the Franconian Basin has never been quantified. Only supra-regional heat flux densities for the Rhenohercynian and Saxothuringian of 65 – 85 mW/m2 were published, based on a few temperature data only from 50 – 300 m depths and literature derived thermal conductivity values. Within the framework of a study on the geothermal potential of NE Bavaria, a new dataset of statistically evident thermo-physical parameters of almost all stratigraphic units of the up to >1600 m thick sedimentary cover rocks of NE Bavaria was created. The newly established data pool comprises measurements of 932 core samples, 661 plug samples and 57 rock fragment samples. Thermal conductivity measurements were performed on dry and water saturated core samples and powder samples from rock fragments. For the determination of gradT, available temperature logs and BHT data of deep wells in NE Bavaria were evaluated. Temperature data were derived from log sections, which are not influenced by artesian upflow. For BHT correction different methods were tested. Heat flux density calculations were performed by the interval method, which is considering the thicknesses of the individual stratigraphic units and their key parameters. In total, temperature data of ten deep wells >500 m in the Franconian Basin were evaluated. Nine of these wells, which are located within the Basin, provide moderate to significantly enhanced geothermal gradients of 3.4 – 4.8 K/100m. Two of these wells do show enhanced gradT in the basement rocks. In contrast, one well at the outer edge of the basin and near the Franconian Line provides a below-normal gradT of 2.5 K/100m. By applying temperature corrected measured thermal conductivities and corrected underground temperatures, the area reveals significantly enhanced heat flux densities between 92 to 128 mW/m2. The deep well with the highest geothermal gradient of 4.8 K/100m provides heat flux densities of 128 mW/m2. The value distribution of heat flux density and geothermal gradients points to a local positive temperature anomaly within an area of about 80 x 50 km. The calculated heat flux densities lie in the order of magnitude of heat flux densities known from the Upper Rhine Rift, which provides heat flux densities around 110 mW/m2 and within the range of heat fluxes of other rift zones worldwide. The exceptionally high heat flux density value of 128 mW/m2 in the centre is based on an undisturbed temperature log which was measured 567 d after the shutdown of the drilling. This time after circulation is sufficient for thermal equilibrium in the borehole. The enhanced gradT in basement rocks of two wells points to a convective thermal regime, the heat source of which is most probably located in the deeper crust. Results of gravimetric modelling in the area, suggest the presence of local granite bodies within the basement rocks and calculations of radiogenic heat production of granitic outcrop analogues shows them sufficient to explain the enhanced gradT in the area.
Keywords: heat flux density; NE-Bavaria; thermal conductivity; thermophysical rock properties

Pore‑fluid‑dependent controls of matrix and bulk thermal conductivity of mineralogically heterogeneous sandstones - Kämmlein, Marion; Stollhofen, Harald (Geothermal Energy, 2019)
For a variety of geothermal engineering applications, the only indirectly determinable matrix thermal conductivity (λm) is frequently used to convert the measured bulk rock thermal conductivity (λb) of air-saturated sandstones to water-saturated conditions. However, the necessary assumption that the absolute value of λm remains constant irrespective of the pore fluid present turns out to be not valid in practice and the explicit control factors on λm have not been demonstrated yet for different pore fluids. A pore fluid-controlled change in the λm value also questions the transferability of empirical proxy models for the estimation of water-saturated λb when they were calibrated on air-saturated samples. This study applies a multiple regression analysis to quantitative mineralogical composition data and porosity (Φ) to identify the controls of the λm for different types of pore fluids (water- vs. air-saturation). In addition, the differences in the calculated λm values resulting from different calculation methods or input data (theoretical geometric mean model or mineralogical composition data) are examined. We further test the suitability of different sandstone properties as potential proxies for the estimation of the λb, with respect to the pore fluid type. Differences in the absolute value of λm of sandstones from different measurement conditions (air- or water-saturated) are most probably related to the formation of authigenic kaolinite in the pore space, originating from the alteration of alkali feldspar. In addition, the thermal properties of the rock matrix are mainly controlled by the volume fractions of the high thermally conductive mineral fractions quartz and dolomite. Empirical models that have solely Φ or P-wave velocity (vp) as variables are not suitable for the prediction of water-saturated λb of sandstones. Instead, quantitative mineralogical data of high thermally conductive mineral phases such as quartz and dolomite have to be included. The easily measureable vp is proposed as a promising proxy for both pore fluid types tested: combined with the total quartz volume/porosity ratio for air-saturated sandstones, and combined with the quartz plus dolomite volume fractions for water-saturated sandstones.<br
Keywords: Matrix thermal conductivity; Bulk thermal conductivity; Pore fluid; Sandstone; Mineralogical composition; Anisotropy

Subsurface granites in the Franconian Basin as the source of enhanced geothermal gradients: a key study from gravity and thermal modeling of the Bayreuth Granite - de Wall, Helga; Schaarschmidt, Anna; Kämmlein, Marion; Gabriel, Gerald; Bestmann, Michel; Scharfenberg, Lars (International Journal of Earth Sciences, 2019)
The Franconian Basin in NE Bavaria is a region of gravity low between the Bohemian Massif in the east and the Kraichgau Terrane in the west. Borehole measurements have identified the northern part of the Franconian Basin as a regional geothermal anomaly and new heat flow calculations give values of > 100 mW/m2. Distinct negative Bouguer anomalies observed in this basin are modeled as granitic intrusions in the Saxothuringian basement that underlies the Permo-Mesozoic units. The interpretation of gravity gradients, in combination with the filtering of gravity data, gives the possible depth constraints of the intrusive bodies. The resulting depths were cross-checked using microstructural studies of quartz veins in the basement rocks (at > 1341 m depth). The quartz shows structures typical for low-temperature plasticity and we infer a deformation temperature of ca. 300 °C. This indicates a considerable pre-Permian uplift of at least 7 km for parts of the Saxothuringian basement and supports depth estimates from gravity data. The heat supply of granitic intrusions by radiogenic decay is modeled considering several scenarios for the geological conditions recovered by the Obernsees borehole (model for conductive heat transfer). The 1390 m-deep drillhole is in a marginal position to the most-pronounced negative Bouguer anomaly. It could be shown that the Saxothuringian basement, including heat-producing granites (heat production rates: 4–6 μW/m3), covered by the insulating sedimentary rocks (1.35 km of Permian to Lower Jurassic units), can account for the enhanced geothermal gradient (38 °C/km) that were measured in the borehole.
CRIS-Team Scopus Importer:2019-07-09
Keywords: Gravity anomalies; Quartz microfabric; Radiogenic heat; Thermal modeling; Variscan granites

The Franconian Basin thermal anomaly, SE Germany revised: New thermal conductivity and uniformly corrected temperature data - Kämmlein, Marion; Bauer, Wolfgang; Stollhofen, Harald (Zeitschrift der Deutschen Gesellschaft für Geowissenschaften, 2020)
Exploration activities for hydrocarbons and thermal waters between the 1960s and 1980s consolidated the assumption of a positive temperature anomaly in the Franconian Basin of SE Germany. However, the geological causes of the temperature high are not known yet. In addition, an up-to-date compilation of temperature data from deep wells and thermal conductivity data of the Permo-Triassic section and of the basement rocks is lacking. In this study, we present a homogenised dataset of uniformly corrected temperature readings from 18 deep wells and new thermal conductivity data of the key strata of the Franconian Basin to constrain the geometry of the anomaly and to calculate reliable conductive surface heat flow densities. We further apply a vertical Péclet number analysis on equilibrated temperature logs for quantifying convective and conductive components in heat transfer. The isotherms of calculated equilibrium temperature gradients >30.0 - 48.9 °C km-1 constrain the presence of elevated temperatures in the Franconian Basin within an area of 100 x 65 km2. The elevated temperatures in the centre of the anomaly presumably originate in the basement but rapidly decrease away from the centre. The geothermal potential of the area is locally high, with surface heat flows exceeding 100 mW m-2 and reaching a maximum of 134(±16) mW m-2 in the central part of the anomaly. The NW-SE elongated shape of the anomaly implies that the strike of the major regional fault system has a significant control on the present-day temperature field. A Péclet number analysis and the correlation of T-log breaks with the new thermal conductivity data prove a predominantly conductive heat transfer regime. However, signatures of convective heat transfer have been proven for the aquifers of the Buntsandstein, Muschelkalk and Keuper groups. The study also reveals significant data gaps in the Franconian Basin, which strongly limit a reliable three-dimensional representation of the temperature field and a further limitation of possible cause(s) of the temperature anomaly. Namely, these are missing temperature data of the basement and a generally low density and the partially low depth level of available temperature dat
Keywords: temperature correction; temperature gradient; temperature anomaly; geothermal energy; heat flow density; Germany

The Franconian Basin thermal anomaly: testing its origin by conceptual 2‑D models of deep‑seated heat sources covered by low thermal conductivity sediments - Kämmlein, Marion; Dietl, Carlo; Stollhofen, Harald (International Journal of Energy and Environmental Engineering, 2019)
This study presents conceptual 2-D models for coupled fluid flow and heat transport simulations of the Franconian Basin in SE Germany to verify the plausibility of different hypothesis on the origin of a local temperature anomaly. The simulated geothermal systems consist of a deep-seated heat source within an impermeable basement (heat-producing granite or enhanced background heat flow), covered by low thermal conductivity sediments. Solely conductive or additional convective heat transport including the presence of a permeable fault was applied. We found that heat transfer in the model setups is strongly controlled by (1) the volume of the heat-producing granite, (2) the amount of the background heat flow, (3) the permeability of the basement rocks, (4) the thermal conductivity contrasts between the sedimentary cover and the basement, and (5) the type of heat transport. If there is no reliable information on these model parameters, a high degree of uncertainty with regard to quantitative statements on the heat transfer in the specific geothermal system can be expected. An equilibrium temperature log from the study area could only be reproduced by (1) an enhanced background heat flow of 0.115 W m2, in combination with a permeable fault zone of permeability 1.0 × 10−13 m2 or (2) a heat-producing granite of large cross-sectional area (300 km2) in combination with an average background heat flow of 0.070 W m2. Moreover, high temperatures were only achieved in the presence of a low conductive, insulating cover above the heat source.<br
Keywords: Thermo-hydraulic modelling; Heat-producing granite; Temperature anomaly; Enhanced heat flow; Fault; Fault permeability

Ursachenforschung zur geothermischen Anomalie in Nordbayern - Drews, Michael; Bauer, Wolfgang; Fazlikhani, Hamed; Stollhofen, Harald; Kämmlein, Marion; Potten, Martin; Thuro, Kurosch; de Wall, Helga (Geothermische Energie, 2019)